2013
DOI: 10.1111/codi.12203
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and lifestyle advice in colorectal cancer survivors – how well are clinicians prepared?

Abstract: There is an awareness of the importance of weight management amongst colorectal cancer clinicians and some indication of advice being provided. However, current perceptions, knowledge and skills suggest scope for further training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 30 publications
2
45
1
Order By: Relevance
“…It is generally believed that 'right to know should obey right to exist', namely considering the survival pressure of patients, we should hide the actual situation of patients to reduce the psychological burden and to protect them to keep a happy life (Chao et al, 2004;Mai et al, 2007). But now, we found that cancer patients' survival right and informed right are unified inseparable as a whole, no matter from the analysis of single factor or multiple factors, the survival not only in all-cause but also in cancer-specific of tumor patients informed groups are far superior to those without informed, Which suggests that cancer patients maybe positive to change their lifestyle and fight against cancer after knowledge of suffering from cancer, and thus to get a longer life expectancy (Meyerhardt et al, 2006a;Campbell et al, 2010;Anderson et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…It is generally believed that 'right to know should obey right to exist', namely considering the survival pressure of patients, we should hide the actual situation of patients to reduce the psychological burden and to protect them to keep a happy life (Chao et al, 2004;Mai et al, 2007). But now, we found that cancer patients' survival right and informed right are unified inseparable as a whole, no matter from the analysis of single factor or multiple factors, the survival not only in all-cause but also in cancer-specific of tumor patients informed groups are far superior to those without informed, Which suggests that cancer patients maybe positive to change their lifestyle and fight against cancer after knowledge of suffering from cancer, and thus to get a longer life expectancy (Meyerhardt et al, 2006a;Campbell et al, 2010;Anderson et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Further complicating this matter is a lack of clarity among health professionals regarding whose role it is to provide alcohol advice. These issues have been found to apply more broadly with respect to other aspects of lifestyle modification, as well as among other cancer survivor populations, which were not explored in this study (Anderson, Caswell, Wells, & Steele, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies indicate that provision of lifestyle advice from cancer care clinicians is low. 151,[180][181][182] Yet clinicians are likely to play an important role in developing motivation because they can inform people with CRC about the associations between physical activity and health (see Chapter 1 for evidence about the benefits of physical activity for people with CRC). Developing this type of motivation may not prove to be too difficult because our qualitative study suggests that many participants with CRC were already aware of the benefits of adopting a healthy lifestyle.…”
Section: Feasibility and Acceptability Of Cardiac Rehabilitation For mentioning
confidence: 99%